Positive Guidance Effect of Ideological and Political Education Integrated With Mental Health Education on the Negative Emotions of College Students - Li, Xueting; Gao, Yanhong; Jia, Yanfeng (Frontiers in Psychology, 2022)
This exploration aims to solve the problems of imperfect psychological health education system and poor educational effects on college students. Here, ideological and political education is integrated with mental health education to investigate the role of collaborative intervention in guiding college students to resist negative emotions. First, an overview is offered of research on ideological and political education, mental health education and negative emotions by the literature survey method. Moreover, a comprehensive investigation is also conducted on research objects, through the questionnaire, to understand the current situation of college students’ negative emotions. And finally, an intervention experiment is taken on college students’ negative emotions by combining ideological and political education with mental health education. The results show that after 10 weeks of intervention experiment by combining ideological and political education with mental health education, there are significant differences in depression, negative emotions, somatization symptoms, and interpersonal problems between the treatment group and the control group (P < 0.01). Besides, there are significant differences in depression, negative emotions, somatization symptoms, and interpersonal problems between sophomores in the treatment group and the control group (P < 0.01). Moreover, there are significant differences in depression, negative emotions, somatization symptoms, and interpersonal problems between males in the treatment group and the control group (P < 0.01). In summary, ideological and political education integrated with mental health education has a positive guidance effect on the negative emotions of college students, greatly improving the negative emotions of the students, helping the students to regulate their emotions, and benefiting their study and life a lot. The purpose of integrating ideological and political education with mental health education is to provide reference for refining the mental health education system of college students and strengthening the positive guidance of college students’ negative emotions.